Mitral Valvotomy An Oldest Cardiac Surgical Procedure For Mitral Stenosis - Rajbhandari, Gambhir Lal (Medical Journal of Shree Birendra Hospital, 1999)
Mitral Valvotomy An Oldest Cardiac Surgical Procedure For Mitral Stenosis